2022
DOI: 10.30798/makuiibf.912445
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electronic Customer Relations Management on Competitiveness and Logistics Performance; A Study on Automotive and Furniture Industry

Abstract: Elektronik müşteri ilişkileri yönetimi (E-MİY), teknolojik gelişmeler sonucu artan e-ticaretin, sadık müşteri kazanma dürtüsünün ve rekabetin bir sonucudur. Teknoloji her geçen gün hızla değiştiğinden piyasadaki firmaların rakiplerinden farklılaşmaları uzun sürmemektedir. Bu noktada asıl farklılığı teknolojiyi kullanarak müşteri ilişkileri geliştiren ve yönlendiren firmalar yakalayabilmektedirler. Bu araştırmanın amacı, E-MİY uygulamalarının rekabet gücü ve lojistik performans üzerindeki etkisini belirlemektir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…To determine the sectors with clustering potential in TRA1 provinces (Erzurum-Erzincan-Bayburt) and to comparatively reveal the competitive advantages of the companies in these sectors. Yaprakli and Aslan (2023) showed that the possible clusters in all three provinces are generally concentrated in the service sector with the results of three-star analysis. Gürler (2023) presented the clustering analysis of countries similar to each other in the travel and tourism sector using the k-means method.…”
Section: Literature Reviewmentioning
confidence: 76%
“…To determine the sectors with clustering potential in TRA1 provinces (Erzurum-Erzincan-Bayburt) and to comparatively reveal the competitive advantages of the companies in these sectors. Yaprakli and Aslan (2023) showed that the possible clusters in all three provinces are generally concentrated in the service sector with the results of three-star analysis. Gürler (2023) presented the clustering analysis of countries similar to each other in the travel and tourism sector using the k-means method.…”
Section: Literature Reviewmentioning
confidence: 76%